ANALISIS PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PERUSAHAAN MASA DEPAN (Studi Empiris Perusahaan LQ 45) - Lena Diyah Prihatiningtiyas, 10.05.52.0059; Susilowati, Yeye (Students Journal of Accounting and Banking, 2014)
The purpose of this research wastoexamine the effect ofIntellectual Capitalon theFinancial Future in companies included in theLQ 45.Intellectual Capital Measurement method Pulicis VAICâ¢ is proxied byVAHU, VACA, STVA. Financial performanceused is DER, NPM, ROE. usingVAHU, VACA and STVA year tis usedto test theDER, NPM, ROEin year t+2. The population of this research is all the companies listed on the Indonesia Stock Exchange and included in the LQ 45between 2008-2010. The sampling technique was done by purposive sampling in order to obtaina representative sample with the criteria that the company is listed on the Stock Exchange and included in theLQ 45 Index for three consecutive years beginning in 2008, 2009, 2010; Publish the audited financial statements are consistent from year 2010-2012, period financial statements ending December 31 each; companies that have positive Â earnings 2008-2012. So there are 54 samples that meet the criteria. The analysis technique used is multiple regression. The results showed that VAHU has a positive and significant effect on the DER, STVA has a negative and significant effect on the DER, where as VACA no effect on DER. VAHU, VACA, STVA has no effect on NPM,. VACA has apositive Â and significant impacton Â ROE, and STVA, VAHU have no effecton ROE.Keywords: Value Added Human Capital (VAHU), Value Added Capital Employed (VACA), Structural Capital Value Added (STVA), Debt to Equity Ratio(DER), Net Profit Margin(NPM), Return On Equity(ROI). Â